Digital Application in EFL Classroom Activity: Using Edmodo to Improve Students’ Writing Performance - Refika Andriani (ELT-Lectura, 2019)
This research aims at improving students’ writing performance on narrative text by using digital application namely edmodo. The method of the research was Classroom Action Research (CAR). The actions were implemented in a cycle. The researcher collaborates with the English teacher as the collaborator in conducting the research. The participants of the research were 20 students of grade tenth Administrasi Perkantoran 1 of SMK Nurul Falah Pekanbaru. The data were taken by using test, observation checklist, field note, and interview. After analyzing the data, it is found that the use of edmodo in writing narrative text activity was able to improve the students’ writing performance. In the other hand, the students were able to generate idea, identify and use various vocabularies, use the appropriate language use and mechanics. The data shows that the students’ score was 80.85. It was improved significantly from the students’ previous daily score, 69. There were several factors that influence the improvement. They are the media, learning activity, and teacher’s ability toward the application usage. Digital application edmodo is an interesting media that can catch the students’ attention so that the students were focus on the use of the media. Learning activity by using edmodo can improve the students’ enthusiasm. They enjoyed learning to write through edmodo with no worry of being mistake. The teachers’ capability of using edmodo motivated and help students to be creative in writing.